Effects of ethyl palmitate on the release of aroma compounds in propanediol–ethanol solution and its mechanisms - Guo, Wei-Wei; Luo, Li-Wen; Wang, Ding-Zhong; Fu, Ying-Jie; Xi, Hui; Sun, Shi-Hao (Frontiers in Chemistry, 2024)
It is known that long-chain esters (LCEs) affect aroma perception, but the mechanism to affect aroma perception is still unclear. In the study, ethyl palmitate (EP), an important LCE in Osmanthus fragrans flower absolute (OFFA), was selected as a target to reveal its role and the mechanism. The release characteristics of 10 aroma compounds from OFFA with/without EP, was obtained by headspace gas chromatography-mass spectrometry (HS-GC/MS) and olfactometry evaluation, respectively. The results showed that EP could change the release behavior of volatile compound in the solution, increased the olfactory detection threshold (ODT), and reduced equilibrium headspace concentrations. According to the Whitman's double layer model, the reason was that EP changed partition coefficients and mass transfer coefficients of the compounds between the liquid phase and the gas phase. This indicated that EP played an important role in the aspect of forming the scent of flavor product. It is very valuable for the style design of flavor product.